2021
DOI: 10.5935/1806-6690.20210041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2,4-D sub-dose on the initial development of common bean crop

Abstract: The adoption of cultures tolerant to synthetic auxins can increase the occurrence of drift of these herbicides, interfering in the development of naturally sensitive cultures, such as beans. The aim of this study was to evaluate the germination and initial development of bean seedlings, using sub-doses of the herbicide 2,4-D. The design of experiment I was completely randomized, with eight treatments and four replications, except for germination, with eight replications. The seeds were sowed in 100 mL of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…Seeds are rich in meristematic and active growth tissues, and since 2,4-D acts on cell division and the metabolism of nucleic acids and proteins, it also damages cell membranes and causes cell death, which explains why seeds are more responsive to auxin (MORO et al, 2021). Massucato et al (2021) also observed damage to the radicle of bean seeds, but they did not correlate with microbial proliferation as occurred in our experiment. In general, although little studied during the germination phase, microbial populations in the soil, substrate, or even endophytes, are critically important during the seedling emergence stage.…”
Section: P á G I N a | 835contrasting
confidence: 53%
See 1 more Smart Citation
“…Seeds are rich in meristematic and active growth tissues, and since 2,4-D acts on cell division and the metabolism of nucleic acids and proteins, it also damages cell membranes and causes cell death, which explains why seeds are more responsive to auxin (MORO et al, 2021). Massucato et al (2021) also observed damage to the radicle of bean seeds, but they did not correlate with microbial proliferation as occurred in our experiment. In general, although little studied during the germination phase, microbial populations in the soil, substrate, or even endophytes, are critically important during the seedling emergence stage.…”
Section: P á G I N a | 835contrasting
confidence: 53%
“…Studies with bean seeds, however, observed that 2,4-D does not have a stimulating effect, even at sub-doses, on seedling emergence and development since seeds treated with 33.50 g/L of 2,4-D had their mass indexes reduced by more than 70%. Moreover, after the application of 67 g/L of 2,4-D in pre-emergence, an injury rate of over 80% was noted (MASSUCATO et al, 2021).…”
Section: P á G I N a | 835mentioning
confidence: 99%
“…Although the phytotoxicity dropped as 2,4-D doses decreased, slight chlorosis was still observed in plants even with the minimum dose (5.23 g ai ha −1 ), causing 20 % phytotoxicity. Massucato et al (2021) found that bean seedlings subjected to subdoses of 2,4-D showed a reduction in germination and length, and increasing concentrations reduced emergence and increased plant injuries. The evolution of phytotoxicity caused by Dicamba in the bean crop was observed in the first evaluation, with little or no difference between evaluation times for most doses.…”
Section: Resultsmentioning
confidence: 97%